Lucretius in Horace's Ars poetica. From words as leaves to the senex laudator temporis acti - Galzerano, Manuel (Ciceroniana On Line, 2023)
The influence of Lucretius’ De rerum natura is clearly felt in Horace’s Ars poetica both at the macro-level of the construction of the text as a didactic work and at the micro-level of the individual iuncturae that compose it. This paper examines two crucial passages of the Epistle to the Pisos: the reflection on the use of neologisms crowned by the similarity between words and leaves (vv. 45-72) and the review of the characters corresponding to the four ages of man (vv. 156-178). The intertextual analysis of the two passages sheds light on the entanglement linking Horace’s treatment of the physical, ethical, and aesthetic doctrines of Lucretius; at the same time, it reveals Horace’s considerable degree of freedom in his constant dialogue with the De rerum natura. The acknowledgement of the centrality of the Lucretian model is also helpful in solving age-old textual problems, allowing for the acceptance of certain debated emendations (e.g. Bentley’s priuos in annos in v. 60) or the confirmation of the integrity the text (e.g. spe longus auidusque futuri in v. 172).